The Impact of School Activities on Road Performance Using PTV Vissim Software Simulation - Liana, Ulwiyah Wahdah Mufassirin; Arif, Muhammad (JSE Journal of Science and Engineering, 2024)
Movement increases along with population growth and economic improvement each year. However, this is not supported by adequate transportation infrastructure, which can lead to congestion and traffic flow. The congestion of Samarinda during peak hours. One such location is Anang Hasyim Street, which has several schools along the road, including Cordova Elementary and Junior High School, SMPN 1, and SMAN 1 Samarinda. Traffic is evident during school hours, both morning and afternoon, along with an increase the number of vehicles and pedestrians. This situation leads to decline in the performance of the road segment. Road performance is a quantitative measurement that describes the conditions occurring on a road segment and serves as a parameter for road performance. This primary data such as road geometric data, traffic volume, and vehicle delays over a specific segment length. Traffic surveys were conducted over three days Monday, February 26, 2024, and Friday and Saturday, March 1-2, 2024. The survey were from 06:30-07:30 WITA,12:00-13:00 WITA, and 15:30-16:30 WITA. The analysis is based on PKJI 2023 and traffic flow simulation using PTV Vissim. The traffic results for 2024 shows the capacity of Anang Hasyim Street is 2968.154 pcu/hour, with the highest vehicle on Monday being 3079.75 pcu/hour and a degree of saturation 0.501 (LoS type A), and side friction of 500.8 incidents per hour. Meanwhile, the forecast for 2034 indicates the capacity remains 2968.154 pcu/hour, vehicle volume of 2202.83 pcu/hour, a degree of saturation 0.74 (LoS type B), and side friction of 563.33 incidents per hour.